Kerry Mitchell, Spirituality and the State: Managing Nature and Experience in America’s National Parks (New York: New York University Press, 2016), xi + 247 pp., $30 (pbk), ISBN: 9781479873012 - Ross-Bryant, Lynn 1944- (2017)
Kerry Mitchell, Spirituality and the State: Managing Nature and Experience in America’sNational Parks (New York: New York University Press, 2016), xi + 247 pp., $30 (pbk),ISBN: 9781479873012
Keywords: national parks; Secularity; Spirituality; Rezension